Adhesin related genes as potential markers for the enteroaggregative Escherichia coli category - Freire, Claudia A.; Rodrigues, Beatriz O.; Elias, Waldir P.; Abe, Cecilia M. (Frontiers in Cellular and Infection Microbiology, 2022)
Enteroaggregative Escherichia coli (EAEC) is an important cause of diarrhea in children and adults worldwide. This pathotype is phenotypically characterized by the aggregative-adherence (AA) pattern in HEp-2 cells and genetically associated to the presence of the aatA gene. EAEC pathogenesis relies in different virulence factors. At least, three types of adhesins have been specifically associated with EAEC strains: the five variants of the aggregative adherence fimbriae (AAF), the aggregative forming pilus (AFP) and more recently, a fibrilar adhesin named CS22. Our study aimed to evaluate the presence of AAF, AFP and CS22-related genes among 110 EAEC strains collected from feces of children with diarrhea. The presence of aggR (EAEC virulence regulator) and genes related to AAFs (aggA, aafA, agg3A, agg4A, agg5A and agg3/4C), AFP (afpA1 and afpR) and CS22 (cseA) was detected by PCR, and the adherence patterns were evaluated on HeLa cells. aggR-positive strains comprised 83.6% of the collection; among them, 80.4% carried at least one AAF-related gene and presented the AA pattern. aggA was the most frequent AAF-related gene (28.4% of aggR+ strains). cseA was detected among aggR+ (16.3%) and aggR- strains (22.2%); non-adherent strains or strains presenting AA pattern were observed in both groups. afpR and afpA1 were exclusively detected among aggR- strains (77.8%), most of which (71.4%) also presented AA pattern. Our results indicate that AAF- and AFP-related genes may contribute to identify EAEC strains, while the presence of cseA and its importance as an EAEC virulence factor and genotypic marker needs to be further evaluated.